Repetitive Bouts of Exhaustive Exercise Induces a Systemic Inflammatory Response and Multi-Organ Damage in Rats - Liao, Peng; He, Qinghua; Zhou, Xuan; Ma, Kai; Wen, Jie; Chen, Hang; Li, Qingwen; Qin, Di; Wang, Hui (Frontiers in Physiology, 2020)
Multiple organ dysfunction syndrome can follow severe infection or injury, but its relationship to exercise is not well understood. Previous studies have observed that prolonged strenuous exercise can lead to transiently increased level and/or activity of markers for systemic inflammatory response and multiple organ damage. However, few studies have analyzed the pathogenesis of the inflammatory response and subsequent multi-organ injury in exhaustive exercise conditions. In this study, we established a rat model of repetitive bouts of exhaustive running (RBER) and investigated its effects on multiple organ damage. Rats were subjected to RBER in either uphill or downhill running modes. Morphologically, RBER causes tissue structural destruction and infiltration of inflammatory cells in the skeletal muscles and many visceral organs. RBER also causes persistent quantitative changes in leukocytes, erythrocytes, and platelets, and changes in the concentration of blood inflammatory factors. These inflammatory alterations are accompanied by increases in serum enzyme levels/activities serve as functional markers of organ damage. In general, RBER in the downhill mode seemed to cause more damage evaluated by the above-mentioned measures than that produced in the uphill mode. A period of rest could recover some degree of damage, especially for organs such as the heart and kidneys with strong compensatory capacities. Together, our data suggest that, as a result of multi-organ interactions, RBER could cause a persistent inflammatory response for at least 24 hours, resulting in tissue lesion and ultimately multiple organ dysfunction.